Comparative Genomic Analysis of Mycobacteriaceae Reveals Horizontal Gene Transfer-Mediated Evolution of the CRISPR-Cas System in the Mycobacterium tuberculosis Complex - Anoop Singh (American Society for Microbiology, 2021)
ABSTRACT Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated (Cas) genes are conserved genetic elements in many prokaryotes, including Mycobacterium tuberculosis, the causative agent of tuberculosis. Although knowledge of CRISPR locus variability has been utilized in M. tuberculosis strain genotyping, its evolutionary path in Mycobacteriaceae is not well understood. In this study, we have performed a comparative analysis of 141 mycobacterial genomes and identified the exclusive presence of the CRISPR-Cas type III-A system in M. tuberculosis complex (MTBC). Our global phylogenetic analysis of CRISPR repeats and Cas10 proteins offers evidence of horizontal gene transfer (HGT) of the CRISPR-Cas module in the last common ancestor of MTBC and Mycobacterium canettii from a Streptococcus-like environmental bacterium. Additionally, our results show that the variation of CRISPR-Cas organization in M. tuberculosis lineages, especially in the Beijing sublineage of lineage 2, is due to the transposition of insertion sequence IS6110. The direct repeat (DR) region of the CRISPR-Cas locus acts as a hot spot for IS6110 insertion. We show in M. tuberculosis H37Rv that the repeat at the 5′ end of CRISPR1 of the forward strand is an atypical repeat made up partly of IS-terminal inverted repeat and partly CRISPR DR. By tracing an undetectable spacer sequence in the DR region, the two CRISPR loci could theoretically be joined to reconstruct the ancestral single CRISPR-Cas locus organization, as seen in M. canettii. This study retracing the evolutionary events of HGT and IS6110-driven genomic deletions helps us to better understand the strain-specific variations in M. tuberculosis lineages. IMPORTANCE Comparative genomic analysis of prokaryotes has led to a better understanding of the biology of several pathogenic microorganisms. One such clinically important pathogen is M. tuberculosis, the leading cause of bacterial infection worldwide. Recent evidence on the functionality of the CRISPR-Cas system in M. tuberculosis has brought back focus on these conserved genetic elements, present in many prokaryotes. Our study advances understanding of mycobacterial CRISPR-Cas origin and its diversity among the different species. We provide phylogenetic evidence of acquisition of CRISPR-Cas type III-A in the last common ancestor shared between MTBC and M. canettii, by HGT-mediated events. The most likely source of HGT was an environmental Firmicutes bacterium. Genomic mapping of the CRISPR loci showed the IS6110 transposition-driven variations in M. tuberculosis strains. Thus, this study offers insights into events related to the evolution of CRISPR-Cas in M. tuberculosis lineages.